2004
DOI: 10.2105/ajph.94.7.1207
|View full text |Cite
|
Sign up to set email alerts
|

HIV Seroprevalence Among Homeless and Marginally Housed Adults in San Francisco

Abstract: HIV seroprevalence was 5 times greater for indigent adults than in San Francisco generally. Sexual behavior predicted HIV infection better than drug use, even among IDUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
155
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 64 publications
1
155
1
1
Order By: Relevance
“…In San Francisco, US, 18 there was found higher HIV prevalence (29.6%) in individuals engaging in homosexual sex (user and non-users of injectable drugs) than in homeless individuals who were injectable drug users and did not engage in homosexual sex (7.7%) and other groups studied (5.0%) of non-homosexual/noninjectable drug users. A high prevalence (17%) was also reported in a probabilistic sample of young (15-24 years) homeless living on the streets of three cities of Ukraine 10 in 2008.…”
Section: Discussionmentioning
confidence: 90%
“…In San Francisco, US, 18 there was found higher HIV prevalence (29.6%) in individuals engaging in homosexual sex (user and non-users of injectable drugs) than in homeless individuals who were injectable drug users and did not engage in homosexual sex (7.7%) and other groups studied (5.0%) of non-homosexual/noninjectable drug users. A high prevalence (17%) was also reported in a probabilistic sample of young (15-24 years) homeless living on the streets of three cities of Ukraine 10 in 2008.…”
Section: Discussionmentioning
confidence: 90%
“…21 In a study conducted in San Francisco, the HIV seroprevalence registered in the homeless population was fi ve times higher than the one in the general population. 14 All the women who were HIV positive and in a homeless condition related exchanging sex for money. An American study showed prevalence of 22.4% for HIV, 53.4% for HBV and 29.7% HCV among female sex workers.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,20 Behavior related to both sexual practice and shared use of injecting drugs may cause the homeless population to be predisposed to hepatitis B infection. 3 The risk of this population to contract hepatitis C also increases when compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 REACH participants received quarterly blood draws and structured interviews. All participants signed a written consent form at the onset of the study and were reimbursed $15 per interview.…”
Section: Methodsmentioning
confidence: 99%